Functional heterogeneity in the superior head of the human lateral pterygoid - Phanachet I. (2014)
The activity of the superior head of the human lateral pterygoid muscle (SHLP) is controversial. Given the non-parallel alignment of some SHLP fibers, the SHLP may be capable of differential activation. The aims were to clarify SHLP activity patterns in relation to location within SHLP. In 18 subjects, SHLP single motor units were intramuscularly recorded at computer-tomography- verified sites during horizontal (e.g., protrusion) and vertical (e.g., opening) jaw tasks (recorded by a jaw-tracking device) and at resting postural jaw position. None of 92 units was active at the resting postural position. Medially located units (21) showed activity during contralateral movement, protrusion, and opening; 5 were also active on jaw closing. There was a significant association between unit location and the number of units active during vertical tasks (i.e., jaw closing and clenching). Analysis of the data suggests differential activation within SHLP and raises the possibility of functional heterogeneity within SHLP.